The Syllabus Design of ESP for The Students of Health Analyst - Nurhidayat Nurhidayat (Hasanuddin University, 2018)
The research was purpose at finding out the need analysis of English for the Health Analyst students, and also designing the syllabus based on the students need. The research was conducted at Academy Health analyst Muhammadiyah Makassar. This research is descriptive research. Data were analyzed using quantitative and qualitative methods. Information on the needs of students is obtained through the provision of questionnaires and interviews to students, alumni, lecturers and stake holder. The findings based on the data analysis indicate that the students state that they need English for communicative competence, the priority in speaking and reading skill in order able to communication and read materials related their field and the student’s purpose in learning English to support to getting a job in the health service institution. By the students need in this study shows that the students give positive response in the health analyst related topic, grammar items and interesting task, method to be consider in apply suggested syllabus design.